Democracia e participação no sistema educacional paulista: do discurso à prática Penápolis, um estudo sobre o processo de reorganização das Diretorias de Ensino - Ronconi, Surlei (2008)
This work aims to unveil the contradictions between the PSDB democratic discourse and the practice of its rulers before the educational reform promoted by this political party, especially in the state of São Paulo. In order to achieve that we read, analyzed and interpreted several documents by PSDB, which guide the political practices of its rulers both in the democratic and in the educational areas. We confronted all this information with the action of party rulers through the laws, decrees and resolutions issued during the terms of President Fernando Henrique Cardoso (FHC) and PSDB governors of the state of Sao Paulo, emphasizing Mário Covas s. Our field research was conducted in the city of Penápolis, which was directly affected by one of the measures adopted when the state educational system was reformed, that is, the closing down of he local board of education in April 1999. The city board of education is the link between local schools and the State Board of Education (SEE) and it was closed down due to restructuring done at the SEE. Due to the services offered by the local board, there was a strong reaction from the community, which put in motion a struggle for the reopening of the local board of education. It was actually reopened on June 29, 2006, now under a different name. Because of this struggle a unique fact happened in Penápolis: the election of the local board chairman instead of his indication by the state government. This was achieved after the formation of a Council composed of local and regional representatives from the town s administration as well as public school teachers. Nevertheless, we conclude that even though the facts that happened in Penápolis point to the possibility of a widening of democratic practices concerning powers of decision, this has not changed the governmental actions as a whole. The SEE still centralizes all decisions what shows the contradiction between PSDB s democratic discourse and governmental practices.